The Prevalence of Genu Varum and Genu Valgum in Overweight and Obese Patients: Assessing the Relationship between Body Mass Index and Knee Angular Deformities: Genu varum and genu valgum in obese patients - Soheilipour, Fahimeh; Pazouki, Abdolreza; Mazaherinezhad, Ali; Yagoubzadeh, Khatereh; Dadgostar, Haleh; Rouhani, Farzaneh (Acta Biomedica Atenei Parmensis, 2020)
Background: Recent studies have shown evidence of a relationship between overweight and obesity with skeletal abnormalities, especially angular knee disorders. Aim of the study: To reveal causal relationship between obesity and skeletal abnormalities. Methods: This study was performed on 280 overweight or obese patients (with BMI > 25kg/m2) who referred to Rasoul Akram hospital in Tehran between 2017 and 2018. Several non-radiographic methods including measuring Q angle, inter-malleoli distance and distance between two knees were used to determine genu varum and genu valgum. BMI was also calculated by dividing the weight by the square of the height. Results: The prevalence of genu varumand genu valgum was 8.6% and 10.0% respectively. There was a significant adverse correlation between the Q angle and BMI. The mean BMI in patients with and without genu varum was 39.07 ± 6.41 kg/m2 and 42.1 ± 2.26 kg/m2, respectively, which was significantly lower in the genuvarum group (P = 0.008). Also, the mean BMI in patients with and without genu valgum was 43.39 ± 3.33 kg/m2 and 41.58 ± 4.61 kg/m2, respectively, which was significantly higher in the genuvalgum group (P = 0.044). Also, there was a direct correlation between BMI of patients with inter-malleoli distance and inverse correlation between BMI and two knees distance. Conclusion: There is a strong and significant relationship between incidence of obesity and genu valgum; therefore, the prevalence of this deformity in obese individuals is predictable. Also, the lower incidence of genu varum in obese people is predictable in our society.